Toxic effects of exposure to microplastics with environmentally relevant shapes and concentrations: Accumulation, energy metabolism and tissue damage in oyster Crassostrea gigas. (15th January 2021) - Teng, Jia; Zhao, Jianmin; Zhu, Xiaopeng; Shan, Encui; Zhang, Chen; Zhang, Wenjing; Wang, Qing
Abstract: Microplastics (MPs) are widely found in coastal areas and oceans worldwide. The MPs are environmentally concerning due to their bioavailability and potential impacts on a wide range of marine biota, so assessing their impact on the biota has become an urgent research priority. In the present study, we exposed Crassostrea gigas oysters to irregular MPs of two polymer types (polyethylene (PE) and polyethylene terephthalate (PET)) at concentrations of 10 and 1000 μg L −1 for 21 days. Accumulation of MPs, changes in metabolic enzyme activity, and histological damage were evaluated, and metabolomics analysis was conducted. Results demonstrated that PE and PET MPs were detected in the gills and digestive gland following exposure to both tested concentrations, confirming ingestion of MPs by the organisms. Moreover, both PE and PET MPs inhibited lipid metabolism, while energy metabolism enzyme activities were activated in the oysters. Histopathological damage of exposed oysters was also observed in this study. Integrated biomarker response (IBR) results showed that MPs toxicity increased with increasing MPs concentration, and the toxic effects of PET MPs on oysters was greater than PE MPs. In addition, metabolomics analysis suggested that MPs exposure induced alterations in metabolic profiles in oysters, with changes in energy metabolism and inflammatory responses. This study reports new insights into the consequences of MPs exposure in marine bivalves at environmentally relevant concentrations, providing valuable information for ecological risk assessment of MPs in a realistic conditions. Graphical abstract: Image 1 Highlights: Microplastics exposure causes energy and lipid metabolism enzyme activity changes in oysters. Microplastics exposure induces histopathological damage in the digestive glands and gills. The IBR results suggest that PET MPs are more toxic to oysters than PE MPs. Metabolomics analysis revealed that MPs cause alteration of metabolic profiles in oysters.